Pengembangan Multimedia Interaktif Berbantuan Canva pada Materi Perkalian Bilangan Cacah di Kelas III SD - Dhevario Rahmadika; Feri Ardiansah; Rajab Vebrian (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Lampung, 2026)
This research was motivated by students' lack of understanding of the material on arithmetic operations of whole number multiplication, low student grades, and limited use of learning media. This study aims to produce and determine interactive multimedia products assisted by Canva for arithmetic operations of whole number multiplication that are valid, practical, and effective. This study is a development research using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The data collection techniques used include interviews, questionnaires, and tests. The data analysis techniques used are the validation questionnaires from the experts, the responses from the students, and the pretest and posttest through normalized N-Gain. Based on the analysis results, the material validity score is 90% with the